2021
DOI: 10.4028/www.scientific.net/ddf.411.79
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Modified Coconut Shell Biochar for Removal of Heavy Metals from Aqueous Solution

Abstract: In this study, coconut shells were converted into biochar via pyrolysis and chemically modified via an acid-base treatment to enrich its adsorption capabilities. Batch experiments were carried out to analyze the adsorption potential of the modified coconut shell (MCSC) or removal of chromium, nickel, and copper from aqueous solution. The chemical modification increased the surface area of MCSC to 185.712 m2/g. Batch adsorption study using MCSC resulted in 99% removal of copper, 95% (nickel), and 39% (chromium)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Compared with other biochar raw materials, coconut shell has the largest surface area and porosity. Meanwhile, the coconut shell has the advantages of low ash content, high density, and high mechanical strength, making it suitable as a raw material for the adsorption of pollutants [ 21 , 22 ]. Shen et al reported that coconut shell biochar has a good removal effect on Cr (VI) due to its rich functional groups [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other biochar raw materials, coconut shell has the largest surface area and porosity. Meanwhile, the coconut shell has the advantages of low ash content, high density, and high mechanical strength, making it suitable as a raw material for the adsorption of pollutants [ 21 , 22 ]. Shen et al reported that coconut shell biochar has a good removal effect on Cr (VI) due to its rich functional groups [ 23 ].…”
Section: Introductionmentioning
confidence: 99%